Extended responsibility through servitization in PSS: An exploratory study of used-clothing sector. Issue 4 (3rd October 2016) - Pal, Rudrajeet
Abstract : Purpose: The global textile-fashion industry is resource inefficient thus requiring higher product-service systems (PSS) intervention. Further, insight of how PSS extends corporate responsibility is rather limited; knowledge of which may contribute towards increased PSS viability. The purpose of this paper is to explore how companies operating with used-clothing PSS extend their responsibilities through servitization. Design/methodology/approach: An exploratory study of seven companies operating with various used-clothing PSS is conducted through semi-structured interviews and supplementary document studies. Findings: Six dominant ways through which servitization drives responsibility in used-clothing PSS are identified. These are through: value-adding services, product leverage, collaborative partnership, information transparency, awareness and platform-enabled networking. Two trade-offs exist in terms of their focus on physical process or digitalization, and developed by honing core competency or collaborative partnership. Further three differentiating attributes underlie these mechanisms for: raising awareness and/or improving transparency, collaboration in value creation and/or in promoting consumption, and product ownership and/or leverage. Research limitations/implications: A wide range of used-clothing PSS exists each in its own way extending responsibility. In-depth studies are required to investigate the relationship between servitization and extended responsibility for diverse PSS-types and on type of responsibilities they address. Practical implications: By identifying the key mechanisms or ways and their underlying characteristics companies can identify new servitization forms and ways to extend their responsibility, identify best practices and establish viability beyond the traditional measures, e.g. financial. Originality/value: So far no studies have investigated the role of servitization in PSS and how it extends corporate responsibility, especially in industries like textile-fashion, where both resource efficiency and responsibility is low.